The Impact of Chair–Team Sociodemographic Dissimilarity on the Relation Between Chair Power and Entrepreneurial Ventures’ R&D Intensity: Evidence From China - Zheng, Yaoyi; Dai, Shufen; Li, Yueting; Su, Yi (Frontiers in Psychology, 2021)
Contemplating the actual leaders of entrepreneurial firms and socio- demographic dissimilarity between leaders and their teams, this study adopts panel data on the entrepreneurial firms of the China's Growth Enterprise Market, and empirically examines the influence of chair power on R&D intensity of entrepreneurial firms from the perspective of social identity. The results indicate that chair power positively affects entrepreneurial firms’ R&D intensity. The chair-team socio-demographic dissimilarity moderates the relationship in such a way that chair power is negatively related to entrepreneurial firms’ R&D intensity only when chair-team socio-demographic dissimilarity is high. The execution of robustness checks authenticate the veracity of the empirical results.